2013
DOI: 10.1097/npt.0000000000000017
|View full text |Cite
|
Sign up to set email alerts
|

Video Games and Rehabilitation

Abstract: Patient nonadherence with therapy is a major barrier to rehabilitation. Recovery is often limited and requires prolonged, intensive rehabilitation that is time-consuming, expensive, and difficult. We review evidence for the potential use of video games in rehabilitation with respect to the behavioral, physiological, and motivational effects of gameplay. In this Special Interest article, we offer a method to evaluate effects of video game play on motor learning and their potential to increase patient engagement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
80
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(110 citation statements)
references
References 97 publications
1
80
0
Order By: Relevance
“…This treatment can also train arm movements within specific details. These games can encourage children to exercise because they become more motivated to perform the therapies12,13,14 ) . In addition, another advantage is that patients can perform exercises at home with less restrictions7, 9, 15, 16 ) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This treatment can also train arm movements within specific details. These games can encourage children to exercise because they become more motivated to perform the therapies12,13,14 ) . In addition, another advantage is that patients can perform exercises at home with less restrictions7, 9, 15, 16 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Li et al12 ) showed that the video game exercise could engage participants’’ attention for a longer period than traditional and tracking exercises. Keith et al13 ) showed that integrating game into therapy can increase the time spent by patients in therapy. In addition, they suggest that through detailed research and development, video games might be a safe, cost-efficient, and effective supplement to conventional physical therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The authors maintain that video game play could be an effective supplement to traditional therapy. Motion controllers can be used to practice rehabilitation-relevant movements, and well-designed game mechanics can augment patient engagement and motivation in rehabilitation [ 23 ].…”
Section: Motivation and Life Satisfactionmentioning
confidence: 99%
“…Exergames are defined as virtual reality video games that provide physical exercise, and have been described and validated as useful tools in neurologic rehabilitation [911] and in the treatment of overweight children [12, 13], among others. However, we could find no comparable reports analyzing exergames in the treatment of idiopathic scoliosis.…”
Section: Introductionmentioning
confidence: 99%
“…This Physiogame, developed by the IT department of the FH JOANNEUM, University of Applied Sciences, Graz, Austria, for this study, combines PSSE with a shooting game [9]. The 3D positions of the trunk and extremity are individually adjusted to the corrective posture desired; the game only continues when the posture is correct.…”
Section: Introductionmentioning
confidence: 99%